2012
DOI: 10.5430/ijba.v3n2p112
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges Facing Small-Scale Women Entrepreneurs: A Case of Kenya

Abstract: The study sought to identify the challenges facing small scale women entrepreneurs in Kenya and initiatives put in place to counter the challenges. The study employed desktop research. MSEs Baseline survey, recorded that 612,848 women in Micro and Small Enterprises (MSEs) in Kenya, accounting for 47.4 per cent of all those in MSEs. The study showed that women tended to operate enterprises associated with traditional women's roles, such as hairstyling. The small and micro enterprises (SMEs) play an important ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 12 publications
2
55
1
5
Order By: Relevance
“…For knowledge, skills, abilities and other attributes (KSAOs), the findings are consistent with research findings of Benard and Victor (2013); Commission (2009); Qureshi et al (2014);Gayathridevi (2014);Mwobobia (2012);Palaniappan, Ramanigopal and Mani (2013);and Niazkar and Arab-Moghaddam (2011). These researchers found that lack of management skills, fear of failure, low level of education, lack of information and knowledge and lack training are barriers to women starting up a business.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For knowledge, skills, abilities and other attributes (KSAOs), the findings are consistent with research findings of Benard and Victor (2013); Commission (2009); Qureshi et al (2014);Gayathridevi (2014);Mwobobia (2012);Palaniappan, Ramanigopal and Mani (2013);and Niazkar and Arab-Moghaddam (2011). These researchers found that lack of management skills, fear of failure, low level of education, lack of information and knowledge and lack training are barriers to women starting up a business.…”
Section: Discussionsupporting
confidence: 87%
“…Past researchers suggest that lack of education act as a barrier for women entrepreneurship (Benard & Victor, 2013;Gayathridevi, 2014;Mwobobia, 2012;Palaniappan, Ramanigopal, & Mani, 2013). The responsibility of women in childcare and household tend to be the reason for women entrepreneurs' low rate in terms of skill and literacy programs training (Richard, 2013).…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The programme helped these entrepreneurs start up more rapidly, while also increasing the profitability and management of their businesses (De Mel et al, 2013). Training and development is also particularly valuable for women micro-entrepreneurs who may have completed only a few years of formal education, as these training programmes can help overcome knowledge gaps in running a successful business (Mwobobia, 2012). At the same time, training programmes need to take due account of the time that women spend on household and care responsibilities, as time-intensive programmes may lead to higher female dropout rates (Valdivia, 2011).…”
Section: Promoting Women's Entrepreneurshipmentioning
confidence: 99%
“…For instance according to the Kenyan National Bureau of Statistics (2014) Enterprising Project (WEP, women may fail to participate in these programs due to family commitments. Mwobobia (2012) noted that when business training is available, women may not be able to take advantage of it because it is held at a time when they are looking after their family. Thus, women may lack opportunities to develop entrepreneurial human capital through education.…”
Section: Gender Considerationsmentioning
confidence: 99%